Prevalence of Anemia and Correlation with Knowledge, Nutritional Status, Dietary Habits among Adolescent Girls at Islamic Boarding School - Aras Utami; Ani Margawati; Dodik Pramono; Diah Rahayu Wulandari (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2022)
Background: Anemia is a globally public health problem, including in Indonesia (22.2%) and it has negative health impacts. Adolescent girls have high risk of anemia. Previous studies reported that adolescent girls at islamic boarding school had low food intake and poor knowledge about nutrition in preventing anemia. Objectives: To assess the prevalence of anemia and to analyze association between knowledge, nutritional status, and dietary habits and anemia in adolescent girls. Materials and Methods: A cross-sectional study was conducted in November 2020 among adolescent girls at islamic boarding school in Semarang. A total of 162 respondents were selected by cluster sampling. Anemia was determined by measuring the hemoglobin level in the blood by Cyanmethemoglobin method. Knowledge and dietary habits were collected through questionnaires. Nutritional status was assessed by measuring weight and height, then classified by body mass index for age using WHO Anthro. Bivariate and multivariate logistic analysis were used to test hypothesis and it was significant if p<0.05. Results: The prevalence of anemia was found to be 17.3%. In the bivariate analysis, overweight was more likely to have anemia (p=0.044). There was no association between father’s education, mother’s education, knowledge, frequency of staple food, breakfast habits, consumption of animal side dishes, consumption of vegetable side dishes, consumption of sweet tea and anemia. Mulitvariate model showed that overweight (OR=3.658; 95%CI=1.224-10.932; p=0.020) and good knowledge (OR=3.652; 95%CI=1.221-10.922; p=0.020) were significant associated with the anemia.Conclusion: Nutritional status and knowledge were significantly associated with anemia among adolescent girls.